The Effect of Artificial Intelligence in Improving Student Learning Achievement in High School - Sugiarso, Brave A.; Nurjamin, Asep; Judijanto, Loso; Firdausiyah, Luluk; Hidayat, Ardian Al (World Psychology, 2024)
Artificial Intelligence (AI) is a process to shape human thinking styles in order to design machines to be able to behave like humans or also called Cognitive Tasks, namely from programmed information data that makes machines able to do work like humans are doing automatically. The purpose of the study is to see how influential Artificial Intelligence is in improving student achievement, especially in high school. This problem utilizes a quantitative approach with a survey model and in-depth interviews. The research survey used by researchers is online-based using the Google Form Platform. The results of this study explain that Artificial Intelligence can assist teachers in creating students who excel in learning, especially at the high school level. The conclusion of the research on the Effect of Artificial Intelligence at the Senior High School level in Improving Student Learning Achievement is that with the help of this Artificial Intelligence Technology, it helps teachers in achieving student competence in the teaching and learning process and students can also improve achievement in the learning process. The limitation of this study is that researchers only conducted research on the influence of Artificial Intelligence in improving student achievement at the senior high school level, researchers hope that future researchers can conduct the same research but at a higher level.